The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.01409
|View full text |Cite
|
Sign up to set email alerts
|

Niche Differentiation of Sulfate- and Iron-Dependent Anaerobic Methane Oxidation and Methylotrophic Methanogenesis in Deep Sea Methane Seeps

Abstract: Methane seeps are widespread seafloor ecosystems shaped by complex physicochemical-biological interactions over geological timescales, and seep microbiomes play a vital role in global biogeochemical cycling of key elements on Earth. However, the mechanisms underlying the coexistence of methane-cycling microbial communities remain largely elusive. Here, high-resolution sediment incubation experiments revealed a cryptic methane cycle in the South China Sea (SCS) methane seep ecosystem, showing the coexistence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 90 publications
2
23
0
Order By: Relevance
“…Therefore, methylotrophic methanogenesis may be an important but previously overlooked methane source in coastal shallow sediments (Conrad, 2020), and trimethylamine, dimethylsulfide, and dimethylsulfoniopropionate may be more common methanogenic substrates in marine sediments than currently thought (Zhuang et al, 2017), especially under higher salinity. Methylotrophic methanogens can co-exist with acetogens, SRB and ANME in OMZ sediments (Bhattacharya et al, 2020) and deep sea methane seeps (Li et al, 2020;Xu et al, 2020), and methanogenesis in the sulfate-reducing zone has been identified in coastal sediments (Maltby et al, 2016). However, whether these microorganisms compete for the same substrates or exist in separate niches remains unclear.…”
Section: Methanogensmentioning
confidence: 99%
“…Therefore, methylotrophic methanogenesis may be an important but previously overlooked methane source in coastal shallow sediments (Conrad, 2020), and trimethylamine, dimethylsulfide, and dimethylsulfoniopropionate may be more common methanogenic substrates in marine sediments than currently thought (Zhuang et al, 2017), especially under higher salinity. Methylotrophic methanogens can co-exist with acetogens, SRB and ANME in OMZ sediments (Bhattacharya et al, 2020) and deep sea methane seeps (Li et al, 2020;Xu et al, 2020), and methanogenesis in the sulfate-reducing zone has been identified in coastal sediments (Maltby et al, 2016). However, whether these microorganisms compete for the same substrates or exist in separate niches remains unclear.…”
Section: Methanogensmentioning
confidence: 99%
“…Although microbial community structures have been investigated at cold seeps in the SCS, nearly all the reports have focused on seepage-affected sediments (Lai et al, 2007;Zhang et al, 2012;Niu et al, 2017;Wu et al, 2018;Cui et al, 2019Cui et al, , 2020Zhuang et al, 2019;Li et al, 2020). Recently, Zhang et al (2020) investigate prokaryotes along the depth profile of the water column.…”
Section: Introductionmentioning
confidence: 99%
“…The 16S rRNA gene phylogeny ( Supplementary Figure S1a ) demonstrates that this microorganism is closely related to ANME-3 archaea detected in Haakon Mosby mud volcano, deep-sea sediments of Monterey Canyon, and some other habitats [ 3 , 4 , 79 ]. The mcrA gene of KA19 ( Supplementary Figure S1b ) phylogenetically belongs to «group f» cluster previously found to be associated with ANME-3 microorganisms [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ,...…”
Section: Resultsmentioning
confidence: 99%
“…The least studied ANME group is ANME-3. ANME-3 has been found mainly in marine ecosystems, including submarine mud volcanoes, deep-marine seeps, shallow and coastal sediments [ 3 , 6 , 7 , 26 , 34 , 35 , 36 , 37 ]. There is a single study report on the detection of ANME-3 in basaltic and granitic rock samples from the deep terrestrial subsurface [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation